Pengaruh Stres Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada PT X: The Effect of Work Stress and Workload on Employee Performance at PT X - Faradilla Aulia; Susan Rachmawati (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The mining industry is characterized by high-intensity work environments and long working hours that may generate work stress and excessive workload, both of which can affect employee performance. This study aims to examine the effect of work stress and workload on employee performance at the Head Office of PT X, one of the largest mining contractors in Indonesia. A quantitative method with a statistical approach was employed, involving all employees of the Human Resources Operation and Development division as the research population. Data were collected through questionnaires and analyzed using partial and simultaneous tests. The results indicate that work stress has a positive and significant effect on employee performance, t-value 4.808 > 2.015, and workload also shows a positive and significant effect, t-value 3.482 > 2.015. Simultaneously, both variables significantly affect performance, F-value 38.075 > 3.210. These findings confirm that properly managed stress and workload can enhance productivity. The study highlights the importance of human resource management policies in stress management and workload distribution to sustain optimal employee performance.